Viral DNA Replication Orientation and hnRNPs Regulate Transcription of the Human Papillomavirus 18 Late Promoter - Xiaohong Wang (American Society for Microbiology, 2017)
ABSTRACT The life cycle of human papillomaviruses (HPVs) is tightly linked to keratinocyte differentiation. Although expression of viral early genes is initiated immediately upon virus infection of undifferentiated basal cells, viral DNA amplification and late gene expression occur only in the mid to upper strata of the keratinocytes undergoing terminal differentiation. In this report, we show that the relative activity of HPV18 TATA-less late promoter P811 depends on its orientation relative to that of the origin (Ori) of viral DNA replication and is sensitive to the eukaryotic DNA polymerase inhibitor aphidicolin. Additionally, transfected 70-nucleotide (nt)-long single-strand DNA oligonucleotides that are homologous to the region near Ori induce late promoter activity. We also found that promoter activation in raft cultures leads to production of the late promoter-associated, sense-strand transcription initiation RNAs (tiRNAs) and splice-site small RNAs (spliRNAs). Finally, a cis-acting AAGTATGCA core element that functions as a repressor to the promoter was identified. This element interacts with hnRNP D0B and hnRNP A/B factors. Point mutations in the core prevented binding of hnRNPs and increased the promoter activity. Confirming this result, knocking down the expression of both hnRNPs in keratinocytes led to increased promoter activity. Taking the data together, our study revealed the mechanism of how the HPV18 late promoter is regulated by DNA replication and host factors. IMPORTANCE It has been known for decades that the activity of viral late promoters is associated with viral DNA replication among almost all DNA viruses. However, the mechanism of how DNA replication activates the viral late promoter and what components of the replication machinery are involved remain largely unknown. In this study, we characterized the P811 promoter region of HPV18 and demonstrated that its activation depends on the orientation of DNA replication. Using single-stranded oligonucleotides targeting the replication fork on either leading or lagging strands, we showed that viral lagging-strand replication activates the promoter. We also identified a transcriptional repressor element located upstream of the promoter transcription start site which interacts with cellular proteins hnRNP D0B and hnRNP A/B and modulates the late promoter activity. This is the first report on how DNA replication activates a viral late promoter.